(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Groundwater samples collected from 15 tube wells of six unions under Puthia upazila of Rajshahidistrict was evaluated their quality for irrigation usage in relation to soil properties and crop growth. Groundwater samples under test were slightly alkaline (pH = 7.10-7.34) in nature and were not problematic for crop production. As regards to TDS, allwater samples were classified as fresh water (TDS<1,000 mg L-1) in quality. EC and SAR values reflected that water samples were medium salinity (C2) and low alkalinity (S1) hazard classes expressed as C2S1. Regarding EC, all collected water samples could be safely used for crops growing on soils with moderate level of permeability and leaching. Groundwater samples were excellent in quality as per SAR and SSP. All water samples were free from RSC and belonged to suitable in category. All groundwater sampleswere hard in quality. The status ofHCO3,Fe, Mn, BO3, SO4, PO4 and Cl ions were recorded below the permissible limit for irrigation and these ions might not create hazardous impact on soil ecosystem. The relationships between chemical parameters of groundwater like EC, TDS, SAR, SSP, RSC and hardness (HT) were established. Significant correlations existed between EC-TDS, EC-RSC, EC-HT, TDS-RSC, TDS-HT, SAR-SSP and RSC-HT. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22201 J. Environ. Sci. & Natural Resources, 7(2): 37-41 2014